The role of auditor assurance and internal control in company performance evaluation by non professional investors - Luciana Spica Almilia; Nurul Mustafida (Universitas Hayam Wuruk Perbanas, 2024)
This study aims to examine the preferences of non-professional investors regarding management disclosures for remediation of internal controls, whether financial statements with internal auditor’s assurance and external auditor’s assurance are more credible than those without assurance. Participants in this study include accounting and management students with knowledge of investment and capital markets, financial statement analysis, and auditing. The total number of research participants is 150 students. The results of the research on pervasive accounts show that (1) there is a significant difference in perceptions of non-professional investors regarding the credibility of financial statements, either without assurance, with internal auditor’s assurance, or with external auditor’s assurance; (2) there is a significant difference in the perception of non-professional investors regarding the level of material weakness of financial statements, either without assurance, with internal auditor’s assurance, or with external auditor’s assurance; (3) there is a significant difference in the perception of non-professional investors regarding the level of material weakness of financial statements, either without assurance, with internal auditor’s assurance, or with external auditor’s assurance; (4) there is no significant difference in the perception of non-professional investors regarding the desire to buy shares, either without collateral, with internal auditor’s assurance, or with external auditor’s assurance.